Health effects of occupational noise exposure on heavy-duty equipment operators and exposed workers in a mining firm in Ghana - Francis Amanle Cudjoe; Douglas Aninng Opoku; Nana Kwame Ayisi-Boateng; Joseph Osarfo; Kofi Sekyere Boateng; Lydon Nii Adjiri Sackey; Edgar Andoh Cobbina; Isaac Kofi Yankson; Alhassan Sulemana (PLoS ONE, 2025)
Background The mining industry is one of the sectors that uses heavy-duty equipment in its daily operations. This exposes miners to undesirable noise levels, increasing their risks of health-related problems. However, published data on the health effects of occupational noise exposure on miners in Ghana are limited, and this can affect potential interventions to promote miners’ health and safety. This study, therefore, assessed noise-exposure levels and associated health-related problems among heavy-duty equipment operators and other exposed workers in a mining firm in Ghana. Methods A cross-sectional study involving 316 randomly selected heavy-duty equipment operators and exposed workers was conducted from 29th March 2023–31st May 2023. Data on socio-demographic and work-related characteristics, including age, mining experience, knowledge of noise-induced hearing loss (NIHL), noise exposure levels and health-related problems, were collected using a pretested questionnaire. Logistic regression models were used to identify significant predictors of health-related problems. Results The mean age of study participants was 33.8 (±7.5) years with a range of 21–60 years. The prevalence of health-related problems in the twelve months before the study was 55.7%. The commonly reported health-related problems included hearing difficulties (84.1%), hearing loss (49.4%), and sleeping difficulties (36.9%). Approximately 68.6% of the workers were exposed to noise levels that were unacceptable. After adjusting for significant covariates, factors such as working experience of 5–9 years (AOR: 4.25, 95%CI: 1.92–9.40), inadequate knowledge of NIHL (AOR:1.78, 95%CI: 1.03–3.09) and exposure to unacceptable noise levels (AOR = 5.52, 95%CI = 2.91–10.48) were independently associated with health-related problems. Conclusion The prevalence of health-related problems among the workers was high. Potential strategies, including a hearing conservation program to promote health and safety among these workers at the workplace, should target reducing the exposure to high noise levels and increasing awareness of NIHL.